Mycobacterium ulcerans disease: Buruli Ulcer - Phillips, Richard Odame (Henry Stewart Talks, 2019)
Buruli ulcer: history, epidemiology and transmission, Clinical manifestation and differential diagnosis, An explanation of the current diagnostic methods, An update on treatment and clinical care, The current Buruli ulcer control strategy, Implications of late treatment, An integrated approach to control of disease